A recombinant sporozoite surface antigen of Theileria parva induces protection in cattle - Musoke, A.J.; Morzaria, S.P.; Nkonge, C.; Jones, E.; Nene, Vishvanath M. (Proceedings of the National Academy of Sciences, 1992)
At present immunization against Theileria parva is by infection with live sporozoites and simultaneous treatment with a long-acting oxytetracycline. This method has major limitations in that live organisms are used and the immunity engendered is parasite stock specific. In an attempt to develop an alternative immunization procedure, the gene encoding p67, a major surface antigen of sporozoites, has been expressed by using the plasmid expression vector pMG1. The gene, which has been characterized previously, encodes 709 amino acid residues, contains a single intron of 29 base pairs, and is only transcribed during sporogony. The recombinant p67 sequences were fused to the first 85 amino acid residues derived from a nonstructural gene (NS1) of influenza virus A. Immunization with a partially purified recombinant antigen emulsified in 3% saponin induced sporozoite neutralizing antibodies in cattle and provided protection in six of nine animals on homologous challenge with T. parva sporozoites. This recombinant antigen is therefore a candidate for development of a vaccine against T. parva.